General Legal Principles and Judicial Review in the European Union: Examination and Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rule of law forms the backbone of the EU legal system. This key principle requires EU institutions to adopt actions that comply with the treaties ratified by the member states. Accordingly, the competencies and authorities of the institutions should be exercised only within the framework of valid legal norms and principles set in the framework of the European Union. To the end, judicial review of the decisions and actions of EU institutions is of paramount significance. This review is achieved by the European courts as guardians of the rule of law. Although the main purpose of judicial review in this legal structure, is to limit the exercise of discretionary powers, and hence similar to that of the legal system of the member states, it has it own unique features, conditions and types.